Informing antimicrobial stewardship: factors associated with inappropriate antimicrobial prescribing in primary care. (10th December 2017) - Singer, Alexander; Fanella, Sergio; Kosowan, Leanne; Falk, Jamie; Dufault, Brenden; Hamilton, Kevin; Walus, Ashley
Abstract: Background: Antimicrobial stewardship (AS) programs promote the optimal use of antimicrobials and safe patient care. With most antimicrobials prescribed in the ambulatory setting, establishing benchmark data is imperative to gauge the impact of future AS initiatives. Objectives: To determine the frequency of potentially inappropriate antimicrobial prescribing in primary care practices in Manitoba, Canada and to assess the association between potentially inappropriate antimicrobial prescribing and patient, prescriber and practice-related factors. Methods: A retrospective cohort study using the Manitoba Primary Care Research Network repository of de-identified Electronic Medical Records from consenting primary care practices. Descriptive statistics and logistic regressions detailed patients with bacterial or viral infections of interest and antimicrobial prescriptions. Results: Eighteen percent ( n = 35 574) of primary care visits for common infections were associated with a potentially inappropriate antimicrobial prescription. Among antimicrobials prescribed to patients diagnosed with bacterial infections, 37.8% ( n = 2168) had a potentially inappropriate antimicrobial prescribed and 19.6% ( n = 1126) had an antimicrobial prescribed for a duration outside of guideline-based ranges. Female patients, younger age and less office visits were associated with potentially inappropriate antimicrobial prescribing for bacterial infections. Among physician visits for viral infection, 15.9% ( n = 29 833) were associated with an antimicrobial prescription. Older patients, those with more comorbidity, more office visits and those who were seen in larger or rural practices, were associated with potentially inappropriate antimicrobial prescribing for viral infections. Conclusions: High frequency of potentially inappropriate antimicrobial prescribing, especially in certain patient populations, suggests the need for coordinated community-based AS programs to optimize prescribing and improve patient care.